METHODOLOGICAL BACKGROUND OF EXPERT ESTIMATION OF INITIAL DATA COMPLETENESS AND QUALITY ACCORDING TO THE CERTIFIED INFORMATION SECURITY SYSTEM - V. K. Fisenko; E. P. Maksimovich; A. B. Stepanyan; V. A. Dmitriev; D. S. Kim; T. S. Martinovich (Informatika)
Problem of information security systems certification is analyzed and the tasks of initial data analysis are carried out. The objectives, indices and decision making criteria, as well as the challenges to be addressed are formulated. It is shown that, in order to improve quality, reduce time and cost of preparation for certification, it is reasonable to use software system for automatization of the process of initial data analysis, presented by the owner of the information system.